Essentials of reformed systematic theology - Beeke, Joel R. (Crossway, 2025)
"Essentials of Reformed Systematic Theology explores the teachings of systematic theology from a perspective that is biblical, doctrinal, experiential, and practical, in the scope of a single volume. It is an abridged and simplified version of the four-volume set, Reformed Systematic Theology, by the same authors"-- Provided by publisher